Closure and the roles of student performance and enrollment characteristics: A survival analysis of charter schools in Ohio's largest urban counties - Elizabeth Anne Gilblom; Hilla I. Sang (Arizona State University, 2019)
In this study, we seek to contribute to the literature on traditional charter school (TCS) closure by examining the potential relationships among racial and socioeconomic enrollment characteristics, TCS age and early adopter status, student achievement and the likelihood of closure within Ohio's "Big 8" Urban Counties (OBEUC). Using life tables and binary logistic regression, we examined 3,204 TCS school years (424 TCS) in OBEUC from the arrival of TCS in 1998 through 2015 to assess these relationships. While the Ohio Department of Education (ODE) reports that poor academic performance is the second most cited reason for TCS closure, we find no evidence that student performance predicts TCS closure in OBEUC. However, we find that compared to TCS with integrated enrollments, TCS with predominantly White or Black enrollments face higher risks of closure in OBEUC, even when controlling for other factors. This lack of a connection between student performance and TCS closure calls into question the argument that TCS closure is evidence that the accountability function of school choice policy is working.